Geothermal energy in Turkey and around the World: A review of the literature and an analysis based on Turkey's Vision 2023 energy targets - Melikoğlu, Mehmet (Pergamon-Elsevier Science Ltd, 2017)
Turkey's geothermal energy potential suitable for electricity generation was estimated at nearly 4500 MW. In Turkey, work on power production from geothermal energy started in the second half of the 20th century. However, capacity build up and investments accelerated after 2000s. This is mostly related to Turkey's staggering economic growth in the last 10 years, which concurrently increased the country's energy demand. Also, renewable energy, especially geothermal energy, legislations passed and laws enacted in the last 10 years eased the process. The subsidies and supports to the private sector also positively affected the development of geothermal power plants. The growth of Turkey's energy market is a part of Turkey's ambitious Vision 2023 energy targets. One of the main aims of which is to produce 30% of Turkey's electricity demand in 2023 from renewable energy sources. However, geothermal energy has the smallest share (in terms of installed capacity) in the Vision 2023 energy targets set at 600 MW by the year 2023 (target, as of 2015, can be modified). This means geothermal power plants could only provide 0.5% of Turkey's installed capacity, which was estimated as 120,000 MW in the year 2023. In this study, it was pinpointed that geothermal energy installed capacity of Turkey reached to 623.9 MW at the end of 2015. This is critically important for the realisation of the Vision 2023 energy targets, and it is the first renewable energy target that has been fulfilled before 2023. Also, in this study, it was suggested to modify the Vision 2023 targets to increase the geothermal energy installed capacity to 1000 MW. By this way, the share of geothermal energy in Turkey's installed capacity of 2023 could rise to nearly 0.8%.
Keywords: Geothermal energy; Renewable energy; Turkey; Vision 2023